2021
DOI: 10.1109/access.2021.3086531
|View full text |Cite
|
Sign up to set email alerts
|

SIR1R2: Characterizing Malware Propagation in WSNs With Second Immunization

Abstract: As an infrastructure of Internet of Things, WSNs (Wireless Sensor Networks) play a more and more important role. However, WSNs are vulnerable to malware and malware can destroy their data security and integrity, which motivates us to explore the role of malware propagation in WSNs. First, according to the actual propagation characteristics of malware in the WSNs and the process of the density change of all node types, we propose an epidemiology-based malware propagation model in consideration of a secondary im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…They suggest the mechanism of the design, distribution, and maintenance of the sensor network. Further, Ye et al [64] proposed a SIR1R2 model that discussed about the mechanism of secondary immunity. To analyse the spreading behaviour of virus in WSN computed the value of basic reproduction number (R 0 ) and found that if R 0 < 1 the malware will no longer survive in WSN, whereas if R 0 > 1 malware will spread in the entire WSN.…”
Section: Related Workmentioning
confidence: 99%
“…They suggest the mechanism of the design, distribution, and maintenance of the sensor network. Further, Ye et al [64] proposed a SIR1R2 model that discussed about the mechanism of secondary immunity. To analyse the spreading behaviour of virus in WSN computed the value of basic reproduction number (R 0 ) and found that if R 0 < 1 the malware will no longer survive in WSN, whereas if R 0 > 1 malware will spread in the entire WSN.…”
Section: Related Workmentioning
confidence: 99%
“…In Ref. [22], the authors proposed the SIR1R2 with secondary immunity to analyze the feature of malware propagation in WSNs. In Ref.…”
Section: Introductionmentioning
confidence: 99%
“…It can not only study the dynamics diffusion process but also position the key nodes and analyze the threshold of virus propagation [14][15][16][17]. The diffusion characteristics of computer network viruses are similar to those of biological viruses, which are latent, infectious, and destructive; thus, the evolution of virus infection among network nodes can be considered, and the SIR model is used to analyze the computer virus diffusion [18][19][20][21][22]. SIR model is introduced to study the mechanism of hacker intrusion diffusion, which has certain innovative significance.…”
Section: Introductionmentioning
confidence: 99%